Non-Covalent Immobilization of C60 in Benzoic Acid Modified Layered Double Hydroxides - Lei Liu, Xiao (Asian Journal of Chemistry, 2013)
Fullerene was non-covalently immobilized in the interlayer of benzoic acid modified layered double hydroxides and the supramolecular structure. The physico-chemical behaviour were characterized by XRD and UV-VIS.